Nepantla squared : transgender mestiz@ histories in times of global shift - Heidenreich, Linda, 1964- (Expanding frontiers., 2020)
"Nepantla Squared maps the lives of two transgender mestiz@s to chart the ways race, gender, sex, ethnicity, and capital function differently in different times. Heidenreich coins the term nepantla² to mark figures who moved between cultures and genders"--